2022
DOI: 10.3390/vetsci9050243
|View full text |Cite
|
Sign up to set email alerts
|

Is Dog Owner Obesity a Risk Factor for Canine Obesity? A “One-Health” Study on Human–Animal Interaction in a Region with a High Prevalence of Obesity

Abstract: Obesity in humans is a growing global problem and is one of the greatest public health challenges we face today. Most researchers agree that, as in humans, the incidence in the companion animal population is also increasing. The aim of this study was to evaluate the risk factors contributing to canine obesity in a region with a high rate of human obesity (Canary Islands, Spain), co-occurrence of obesogenic risk factors, and a canine population with a high percentage of unneutered dogs. We have focused on owner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
0
9
0
3
Order By: Relevance
“…When it comes to an excess of body fat in dogs, the protracted imbalance between food intake and energy expenditure must be considered ( Courcier et al, 2010 ), as well as factors related to changes in eating behavior and voluntary physical activity, such as neutering and ageing ( Courcier et al, 2010 ; Kawauchi et al, 2017 ; Suarez et al, 2022 ). Such factors might have affected energy expenditure in client-owned OB dogs in this study, which had different age and neuter status.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to an excess of body fat in dogs, the protracted imbalance between food intake and energy expenditure must be considered ( Courcier et al, 2010 ), as well as factors related to changes in eating behavior and voluntary physical activity, such as neutering and ageing ( Courcier et al, 2010 ; Kawauchi et al, 2017 ; Suarez et al, 2022 ). Such factors might have affected energy expenditure in client-owned OB dogs in this study, which had different age and neuter status.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, Hoffman et al [ 75 ] reported that comorbidities behind chronic conditions such as obesity, arthritis, hypothyroidism, and diabetes reported in humans were also present in 73,835 canines and that those dogs showed a positive association between age and the number of morbidities ( p < 0.001). Other studies have revealed that obesity in dogs (137/198) is closely linked to the alimentary habits of their owners, finding that the 79.8% of dogs from overweight owners (114 persons) were obese ( p < 0.001) [ 76 ]. Therefore, studies of these animals could provide information on disease interaction.…”
Section: Animal Models and Their Application In Distinct Fields Of Cu...mentioning
confidence: 99%
“…Para Montoya-Alonso et al (2017), há uma relação significativa (p <0,001) entre tutores e cães, obesos ou com sobrepeso, em relação à gordura corpórea, demonstrando que o comportamento e hábitos alimentares similares, bem como baixa ou ausência de prática de atividade física são fatores relevantes para o desenvolvimento dessa relação não saudável. Da mesma forma, Suarez et al (2022) afirmaram que os tutores tendem a reproduzir suas atitudes e comportamentos pessoais em seus animais de companhia. Em cães obesos, esse comportamento é referido como um estilo de vida obesogênico, caracterizado por alimentação em excesso e inatividade (Suarez et al, 2022).…”
Section: A) Fatores Relacionados Ao Manejo E Ambienteunclassified
“…Da mesma forma, Suarez et al (2022) afirmaram que os tutores tendem a reproduzir suas atitudes e comportamentos pessoais em seus animais de companhia. Em cães obesos, esse comportamento é referido como um estilo de vida obesogênico, caracterizado por alimentação em excesso e inatividade (Suarez et al, 2022). Diferentemente, Muñoz-Prieto et al (2018) não apontaram correlação direta entre a prevalência de obesidade em tutores e cães, sendo que este fato pode ser explicado pelas diferentes populações estudadas e pelos métodos utilizados.…”
Section: A) Fatores Relacionados Ao Manejo E Ambienteunclassified